1990
DOI: 10.1063/1.103238
|View full text |Cite
|
Sign up to set email alerts
|

Flexible superconducting whiskers of the Li-doped Bi-Sr-Ca-Cu oxide

Abstract: Flexible Li-doped Bi-Sr-Ca-Cu-O superconducting whiskers have been prepared by heating a glassy melt-quenched plate in a stream of O2 gas. The whiskers show a resistance drop at 110 K with a zero resistance at 81 K. These values are higher than those of the Pb-doped Bi-Sr-Ca-Cu-O whiskers by 5 and 11 K, respectively. The doping of Li is effective to raise Tc for both the 2212 phase and the 2223 phase. The Jc values of the Li-doped whiskers are 30 000 A/cm2 at 77 K and 300 000 A/cm2 at 66 K in a zero magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…For example, Pb doping of Bi-Sr-Ca-Cu-O and Tl-Sr-Ca-Cu-O superconducting systems induces a partially melted liquid phase that eases the diffusion of the elements to form the high-T c phases and to increase their critical current (I c ) [7,8]. Li doping of Bi-based superconductors have been also studied [9][10][11]. Li doping reduces the melting and formation temperatures of the Bi-based superconductors leading to shorter annealing times.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Pb doping of Bi-Sr-Ca-Cu-O and Tl-Sr-Ca-Cu-O superconducting systems induces a partially melted liquid phase that eases the diffusion of the elements to form the high-T c phases and to increase their critical current (I c ) [7,8]. Li doping of Bi-based superconductors have been also studied [9][10][11]. Li doping reduces the melting and formation temperatures of the Bi-based superconductors leading to shorter annealing times.…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that these materials are highly flexible, and they can be bent elastically to form a different shape with various radius. 1,2 At the same time, they have high mechanical strength and large critical current density compared to the polycrystalline materials. [3][4][5] Many attempts have been done to fabricate single crystal superconducting whiskers using different superconducting systems and techniques.…”
Section: Introductionmentioning
confidence: 99%
“…An onset temperature of 98 K has been reported for a Bi-Sr-Ca-Cu oxide 2212 phase in which lithium is partially substituted for copper [12]. Furthermore, the inclusion of lithium in superconducting Bi-Sr-Ca-Cu oxide flexible whiskers, prepared by heating a melt-quenched plate in oxygen, is effective in raising the Tc, in both the 2212 phase and the 2223 phase [13]. Electrochemical intercalation affords not only the advantage of room-temperature implementation, but also the ease of control of the level of doping in the superconductor.…”
Section: Introductionmentioning
confidence: 99%